Konsep Dasar Sistem Sosial Indonesia Dan Masyarakat Sebagai Suatu Sistem - Sertiawan, Nerisa; Nasution, Ayu Lestari; Syafira, Ade Chia (Faidatuna, 2023)
social system and society as a system. This research uses qualitative methods with a library research approach (Liberary Research). The subject of this research is society. Data collection techniques by collecting references from books, journals, review literature and relating to the journal to be studied. While the data analysis technique used is data reduction, data presentation and drawing conclusions. Based on the research results, it has been shown that social systems can be formed because of a general assessment that has become an agreement among community groups. The basic concept of the Indonesian social system and society as a system is related to education which is an inseparable part of society by describing the character and characteristics of society that will be developed in the present and in the future. In addition, the basic concept of the Indonesian social system and society is related to everything related to the flow of the system of living together and living in society from individuals or groups of people which already includes structure, organization, social values, and life aspirations and how to achieve them